Estratégias para tratamento seletivo de endoparisotoses em ovinos na região semiárida - Monteiro, Hudson de Queiroz (Universidade Federal Rural do Semi-Árido, 2019)
Sheep farming is an old source of income and of quality animal protein for the Northeast, and according to the 2017 Agro Census (IBGE) the northeast was the only Brazilian region where the number of animals of this species increased compared to the 2006 Agro Census, showing that there is room for development of the practice in the semiarid. However, the problem with gastrointestinal parasites remains a major obstacle to the profitable production of these animals. Several studies show that helminths are resistant to most commonly used compounds, so it is essential to change the programs of herd treatment. The use of selective treatments is a good alternative for reducing the number of treated animals, the costs of buying anthelmintic and increasing the refugia population of these helminths. Thus, the objective of this study was to evaluate the efficiency of criteria such as of fecal egg count (FEC), Famacha© score and hematocrit in the implementation of selective treatment for antihelmintic treatment in sheep without racial pattern defined in semiarid environment. Sixty adult females without defined racial pattern were used, divided into 4 groups according to the treatment criterion: 1 control group, 2 Famacha© group, 3 FEC group and 4 hematocrit group. From these animals, feces, Famacha© score and blood were collected. From the collected feces, the FEC was made and through the blood samples were made the leukocyte count, lymphocytes, medium cells, granulocytes, lymphocytes percentage, average cells percentage, granulocytes percentage, red blood cells count, hematocrit, mean corpuscular volume, amplitude distribution of red blood cells and platelets. Two collections were made at an interval of 28 days. Between collections, 10% sodium closantel was administered according to the treatment criteria of each group. The animals of the control group showed no statistical differences in the data comparing the two collections. The Famacha© group had the largest number of animals treated, 9. After the use of the drug most had a reduction in Famacha© score, FEC and increased hematocrit. In the FEC group only 1 animal received anthelmintic treatment, and this presented reduction in Famacha© score, reduction of FEC and increase of hematocrit. In the hematocrit group no animals were treated and they also showed no statistical differences between the data from the two collections. It was concluded that the FEC and hematocrit were inversely proportional due to the prevalence of H. contortus in the property and that the criteria for antihelmintic treatment should be analyzed together in the following order: Famacha©>FEC>hematocrit because there are animals with high Famacha© score but do not have other treatment criteria that could be endoparasitic resistant or resilient animals.
Monografia
Keywords: Anti-helmíntico; Ovinocultura; Haemonchus contortus; Famacha©; Anthelmintic; Sheep farming; Haemonchus controtus; Famacha©; CIENCIAS AGRARIAS::MEDICINA VETERINARIA